Tenocyte-imprinted substrate: a topography-based inducer for tenogenic differentiation in adipose tissue-derived mesenchymal stem cells. (16th April 2020) - Haramshahi, Seyed Mohammad Amin; Bonakdar, Shahin; Moghtadaei, Mehdi; Kamguyan, Khorshid; Thormann, Esben; Tanbakooei, Sara; Simorgh, Sara; Brouki-Milan, Peiman; Amini, Naser; Latifi, Noorahmad; Joghataei, Mohammad Taghi; Samadikuchaksaraei, Ali; et al.
Abstract: Tendon tissue engineering based on stem cell differentiation has attracted a great deal of attention in recent years. Previous studies have examined the effect of cell-imprinted polydimethylsiloxane (PDMS) substrate on induction differentiation in stem cells. In this study, we used tenocyte morphology as a positive mold to create a tenocyte-imprinted substrate on PDMS. The morphology and topography of this tenocyte replica on PDMS was evaluated with scanning electron microscopy (SEM) and atomic force microscopy. The tenogenic differentiation induction capacity of the tenocyte replica in adipose tissue-derived mesenchymal stem cells (ADSCs) was then investigated and compared with other groups, including tissue replica (which was produced similarly to the tenocyte replica and was evaluated by SEM), decellularized tendon, and bone morphogenic protein (BMP)-12, as other potential inducers. This comparison gives us an estimate of the ability of tenocyte-imprinted PDMS (called cell replica in the present study) to induce differentiation compared to other inducers. For this reason, ADSCs were divided into five groups, including control, cell replica, tissue replica, decellularized tendon and BMP-12. ADSCs were seeded on each group separately and investigated by the real-time reverse transcription polymerase chain reaction (RT-PCR) technique after seven and 14 days. Our results showed that in spite of the higher effect of the growth factor on tenogenic differentiation, the cell replica can also induce tenocyte marker expression (scleraxis and tenomodulin) in ADSCs. Moreover, the tenogenic differentiation induction capacity of the cell replica was greater than tissue replica. Immunocytochemistry analysis revealed that ADSCs seeding on the cell replica for 14 days led to scleraxis and tenomodulin expression at the protein level. In addition, immunohistochemistry indicated that contrary to the promising results in vitro, there was little difference between ADSCs cultured on tenocyte-imprinted PDMS and untreated ADSCs. The results of such studies could lead to the production of inexpensive cell culture plates or biomaterials that can induce differentiation in stem cells without growth factors or other supplements.